Resilience in Survivors of Child Sexual Abuse: A Systematic Review of the Literature. (October 2015) - Domhardt, Matthias; Münzer, Annika; Fegert, Jörg M.; Goldbeck, Lutz
Objective: This review article summarizes empirical research on resilience in survivors of child sexual abuse (CSA) and discusses protective factors that are associated with adaptive functioning in spite of sexual victimization. Methods: A literature search to identify studies published up to November 2013 was performed within the databases PsycINFO, MEDLINE/PubMed, Web of Science, and PSYNDEXplus. Additional relevant studies were retrieved using a snowball technique. A total of 37 articles met the inclusion criteria and were included in the final sample. Results: In the studies included in this review, the percentage of CSA survivors who were found to have a normal level of functioning despite a history of sexual abuse ranged from 10% to 53%. The protective factors that had the best empirical support were found to be education, interpersonal and emotional competence, control beliefs, active coping, optimism, social attachment, external attribution of blame, and most importantly, support from the family and the wider social environment. Conclusions: Preventive and clinical interventions for survivors of CSA should utilize psychoeducation and cognitive strategies that are adapted to the developmental level of the victim and that seek to enhance social support from significant others. Future research should focus on longitudinal research designs considering resilience rather as a dynamic process with multiple dimensions in a social and developmental context.